Leguminicolous fungi associated with some seeds of Sudanese legumes - SOHAIR A. ABDULWEHAB; SAIFELDIN A. F. EL-NAGERABI; ABDULQADIR E. ELSHAFIE (Society for Indonesian Biodiversity, 2015)
Abdulwehab SA, El-Nagerabi SAF, Elshafie AE. 2015. Leguminicolous fungi associated with some seeds of Sudaneselegumes. Biodiversitas 16: 269-280. The mycoflora associated with seeds evidently deteriorate seed viability, germination, emergenceand plant growth performance leading to apparent losses in production and productivity. In the present investigation, seedborne fungi ofsix legumes were screened. Twenty six species of fungi from 14 genera were isolated from this seeds. Of these isolates, 6 species arenew reports to the mycoflora of Sudan, whereas some species are new records to the mycoflora of these legumes. These include 6species for Cajanus cajan, Cicer arietinum (10 species), Dolichos lablab (7 species), Medicago sativa (8 species), Phaseolus vulgaris(10 species), and Vigna unguiculata (11 species). The seeds are obviously contaminated with saprophytic and pathogenic fungi (17-64%) which evidently inhibited seed germination (41-86%), and seedling emergence (29-81%). The Alternaria, Aspergillus andFusarium (4 species each) were the most prevalent fungi followed by Curvularia, Drechslera (3 species), Fusariella, Ulocladium (2species) and one species for the remaining genera (Aureobasidium, Acremonium, Memnoniella, and Rhizopus). Hence, there is a highneed for establishment of standard seed testing methods with strong legislations in order to meet the international quarantine regulations.The use of certified seeds by the farmers is recommended.